No passengers beyond this point - Choldenko, Gennifer (New York : Scholastic, 2011)
With their house in foreclosure, sisters India and Mouse and brother Finn are sent to stay with an uncle in Colorado until their mother can join them, but when the plane lands, the children are welcomed by cheering crowds to a strange place where each of them has a perfect house and a clock that is ticking down the time.
Keywords: Siblings -- Juvenile fiction; Space and time -- Juvenile fiction; Fantasy fiction